Sistem Informasi Dokumentasi Surat (Studi Kasus Di PT. Pertamina Depot Bula) - Matatula, Frengklin (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2016)
In managing documents PT.Pertamina of Depot Bula at the time still in manual and less efficient in recording and data search letters that take a considerable time in all processes. Therefore, it is required by the software to help manage data effectively and efficiently letter. To help resolve the constraints faced by the author takes the title "information system documentation letter". With this information system is expected to last letter of information system documentation to be better than ever. After this letter information system documentation created and based on the desire of the results of PT. Pertamina Depot Bula with their conclusion that the letter information system documentation process is becoming more efficient, fast and easy because in giving the number of letters assistant will no longer need to open a file of letters and numbers letter will be recorded automatically at the time assistant to open a new mail. Therefore, the numerical gain minimizing mistakes letter. In the letter, the data search process will be easier to fast and without the need to open the file documentation as well as data security is also more secure with their password gift. Another database keeps bending to mind is information system documentation this letter is much more effective.